The Yuen’s Dimension-Based Cultural Diversities in the ELT Textbook For Senior High School Students - Setyawaningsih, Sari Putri; Setyono, Budi; Rofiq, Annur (English Education Study Program, 2021)
The present study uses critical discourse analysis (CDA) to examine the representation of cultural diversities in the first year of senior high school English textbook published by a non-government publisher. Data of the present study are texts and pictures that represent cultural diversities in an Indonesian ELT textbook. The findings revealed that there are four cultural categories based on Yuen’s cultural dimensions (i.e product, practice, person, and perspective) coming from inner, outer, and expanding circle countries. The implication is that the visual materials must be balanced with the verbal materials. Keywords: Critical discourse analysis, cultural diversities, ELT textbook, senior high school, Indonesia.